Simulating urban traffic scenarios : 3rd SUMO Conference 2015 Berlin, Germany - Behrisch, Michael, 1976-; Weber, Melanie (Of Deutsches Zentrum für Luft- und Raumfahrt) (Springer, 2019)
This contributed volume contains the conference proceedings of the Simulation of Urban Mobility (SUMO) conference 2015, Berlin. The included papers cover a wide range of topics in traffic planning and simulation, including intermodal simulation, intermodal transport, vehicular communication, modeling urban mobility, open data as well as autonomous driving. The target audience primarily comprises researchers and experts in the field of mobility research, but the book may also be beneficial for graduate students.- Resumé vydavatel
Keywords: městská doprava; kombinovaná doprava; modelování a simulace; automatické řízení; urban transportation; combined transport; modeling and simulation; automatic control; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences